THEME: DEVELOPING LISTENING AND SPEAKING SKILLS INTENSIVELY - Safarova Dildora; Rahmonqulova Ruxshona (Ustozlar uchun, 2025)
This article explores the importance of intensive practice in developing listening and speaking skills in a foreign language. It highlights the significance of exposure to authentic language materials, active listening, and speaking practice with native or non-native speakers. The article emphasizes the role of immersion, technology, and goal-setting in enhancing fluency and proficiency. By incorporating structured and varied activities, such as pronunciation drills, real-time conversations, and media consumption, learners can build confidence and refine their communication abilities. The article stresses the need for perseverance and feedback to ensure consistent improvement in listening and speaking skills, ultimately enabling learners to engage effectively in real-world situations.